Antimicrobial Property of Musa Plant Extract Against Bacteria Isolated from Wound on The Extremities - Mohd Rifhan, Syahmi; Haniza, Sahdi; Mohamad Zaki, Mohd Amin; Isabel Lim, Fong; Khong, Heng Yen (Malaysian Orthopaedic Association (MOA), 2023)
Herbal medicines have a long history of usage in wound care management. It was discovered that Musa plant extract seem to have antimicrobial property. Current study was carried out to investigate the antimicrobial properties of Musa paradisiaca plant extract against the microorganism isolated from infected wound.